THE REORGANIZATION OF FEDERAL ACCOUNTING. - Mansfield, Harvey C. (The Accounting Review, 1940)
Abstract It is the purpose of this paper to discuss some of the outstanding problems of organization and procedure in the conduct of the accounting functions of the national government above the departmental level, that is to say, of central accounting and control as distinguished from the fiscal administration of individual operating agencies. The theme of this paper is the development of improved practices, and while few citizens are interested in forms of government as such, abstracted from the results they tend to foster, significant progress toward essential improvements in practice in this field is inextricably bound up with changes in the machinery of central financial control. Present practices are the logical result of present organization. The starting point is, then, an analysis of that system. The reorganization bills before the U.S. Congress in 1938 contained sweeping proposals deigned to meet the kind of difficulties that have been noticed here: the divorce of control and audit, vesting the one in an executive agency and the other in an independent office safeguarded as the Comptroller General now is; and the establishment of a Congressional Joint Committee on Public Accounts.